Determining the Arterial Occlusion Pressure for Blood Flow Restriction: Pulse Oximeter as a New Method Compared With a Handheld Doppler. Issue 4 (29th April 2022) - Lima-Soares, Fernanda; Pessoa, Kassiana A.; Torres Cabido, Christian E.; Lauver, Jakob; Cholewa, Jason; Rossi, Fabrício; Zanchi, Nelo E.
Abstract: Lima-Soares, F, Pessoa, KA, Torres Cabido, CE, Lauver, J, Cholewa, J, Rossi, FE, and Zanchi, NE. Determining the arterial occlusion pressure for blood flow restriction: Pulse oximeter as a new method compared with a handheld Doppler. J Strength Cond Res 36(4): 1120–1124, 2022—In laboratorial and clinical settings, the use of Doppler ultrasound equipment has been considered the gold standard method to determine arterial occlusion pressure (AOP). However, the use of Doppler equipment is inherently limited to the technical expertise needed to perform AOP measurements. To overcome the technical difficulties of the use of Doppler equipment use in the determination of AOP, a simpler and less subjective methodology would be helpful for blood flow restriction (BFR) practitioners. In this regard, portable pulse oximetry has been largely used in clinical practice for measuring systolic pressures, as well as loss or recovery of pulse, with results similar to those observed with the use of Doppler equipment. For such purposes, the AOP from young male and female subjects was evaluated after different body positions (standing, seated, and supine positions). Loss of capillary blood flow or AOP was readily determined by simple visual inspection for the pulse oximeter and loss of sound for the Doppler equipment. The results presented herein strongly suggest the use of the portable pulse oximetry equipment as reliable, when compared with the handheld Doppler (seated k = 0.962, standing k = 0.845, and supine k = 0.963 and seated rs = 0.980, standing rs = 0.958, and supine rs = 0.955). Because AOP measurement by pulse oximetry is relatively easier to perform and financially more accessible than handheld Doppler equipment, BFR practitioners may benefit from this new methodology to measure AOP, thus determining individualized restriction pressures.